Pouring sealant for battery pack of new energy electric vehicle and preparation method of pouring sealant

By optimizing the ratio of polyether polyols, polyester polyols, flame retardants and inorganic fillers, combined with the use of isocyanates, the flame retardancy, aging resistance and hardness problems of the potting adhesive for battery packs for new energy electric vehicles have been solved. The comprehensive effect of low density, low thermal conductivity, high hardness and excellent aging resistance is achieved.

CN119220213APending Publication Date: 2024-12-31JIANGSU CHANGSHUN POLYMER MATERIAL INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310783485.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Polyurethane potting glue for new energy electric vehicles is difficult to take into account the flame retardant performance of UL 94V0 and the aging resistance of 1000h under dual 85 conditions. At the same time, the hardness is not high enough, and the high thermal conductivity of traditional potting glue makes it unsuitable for winter use.

Method used

The ratio of component A and component B is 100:45 to 55. Component A includes polyether polyol, polyester polyol, flame retardant, inorganic filler and additive. Component B is isocyanate, and is dispensed. The machine is mixed and cured at room temperature to optimize viscosity and flowability to meet the requirements of low density, low thermal conductivity, high hardness, flame retardancy and aging resistance.

Benefits of technology

The prepared potting glue for battery packs for new energy electric vehicles has low density, low thermal conductivity, high hardness, excellent UL 94V0 flame retardant and 1000h aging resistance under dual 85 conditions, which improves the safety and range of the battery pack. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004311487430000041
    Figure BDA0004311487430000041
  • Figure BDA0004311487430000051
    Figure BDA0004311487430000051
  • Figure BDA0004311487430000061
    Figure BDA0004311487430000061
Patent Text Reader

Abstract

The invention relates to a pouring sealant for a battery pack of a new energy electric vehicle and a preparation method of the pouring sealant, and mainly solves the technical problems that a polyurethane pouring sealant in the prior art is difficult to simultaneously consider UL 94V0 flame retardant property and double 85 (the temperature is 85 DEG C and the relative humidity is 85%) 1000h aging property, and the hardness is not high enough. The pouring sealant for the new energy electric vehicle battery pack is composed of a component A and a component B, and the mass ratio of the component A to the component B is 100: (45-55); the component A is prepared from the following components in parts by weight: 15 to 20 parts of polyether polyol I; 10 to 15 parts of polyester polyol; 3 to 6 parts of polyether polyol II; 10 to 18 parts of a flame retardant; 38-45 parts of an inorganic filler; 0.4 to 1 part of an auxiliary agent; 2-4 parts of silicone oil; 0.3 to 0.9 part of water; the component B is isocyanate; according to the technical scheme, the problem is well solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical synthesis, and in particular relates to a potting adhesive for a new energy electric vehicle battery pack and a preparation method thereof. Background Art

[0002] With the increasing requirements of national energy conservation and environmental protection policies, the application and development of new energy sources have received extensive attention; new energy electric vehicles are a major direction for solving energy, environmental protection, urban transportation and other issues, and are also the mainstream trend of the development of the automobile industry. At present, new energy electric vehicles generally face technical problems such as short power battery life, short driving range, poor battery safety performance, and poor environmental adaptability.

[0003] In order to protect the vehicle battery module, manufacturers usually fill the gaps between the battery shell and the battery cells with potting glue, intending to provide mechanical stability and impact resistance for the battery module, while also taking into account adhesion, flame retardancy, high temperature resistance, hydrolysis resistance and electrical performance. At present, the power battery accounts for up to 30% of the weight of the whole new energy vehicle, and its lightweight is also very important, which is related to the improvement of the cruising range of new energy vehicles. Therefore, the low-density requirements for battery module potting glue are getting higher and higher.

[0004] Polyurethane potting glue has a low density and good impact resistance. Using polyurethane potting glue to fill the battery can well meet the safety requirements of the battery and is light in weight. At the same time, the harshness of the use environment of new energy batteries leads to high requirements for the flame retardancy, mechanical properties, hydrolysis aging resistance, high and low temperature impact resistance and dimensional stability of the potting glue products. However, the flame retardancy and moisture and heat aging resistance of conventional polyurethane potting glue are relative; it is difficult to meet the flame retardancy (UL94V0 flame retardant grade) and moisture and heat aging resistance at the same time. In addition, conventional battery pack potting glue has high thermal conductivity, which is used to resist high temperature, heat conduction and heat dissipation, but now car companies have independent cooling systems, so it is necessary to design and develop potting glue with a high thermal conductivity coefficient, which can have a good insulation effect when used in winter and improve the cruising range.

[0005] Chinese patent CN115651596A discloses a low-density high-thermal-conductivity polyurethane potting glue and its preparation method. The low-density high-thermal-conductivity polyurethane potting glue is mixed by component A and component B in a mass ratio of 100:(16-25); component A includes the following raw materials in mass fractions: 20-43 parts of polymer polyol, 0-5 parts of small molecule chain extender, 50-80 parts of modified thermal conductive powder, 3-5 parts of environmentally friendly halogen-free flame retardant, 0-0.6 parts of coupling agent, 0-0.05 parts of catalyst, 0-1 parts of hydrolysis resistance agent, 1-5 parts of water absorbent, 0-0.5 parts of defoamer, 0-0.1 parts of anti-settling agent, and 0-0.5 parts of color paste; component B includes the following raw materials: in terms of mass percentage of component B, 0-20% of polyether polyol, 80%-100% of diisocyanate, and 0-20% of viscosity reducer. The invention has the characteristics of low density and high thermal conductivity, low viscosity, and excellent operating performance. The patent does not disclose any specific data on the flame retardancy and moisture-heat aging resistance of the preparation.

[0006] Chinese patent CN 113717347A discloses a polyurethane foam potting glue for battery cells and a preparation method thereof. The polyurethane foam potting glue composition for battery cells described in the invention is composed of a polyol A component and an isocyanate B component, wherein the raw materials of the polyol A component are special polyester polyols, vegetable oil-modified polyols, flame retardant polyols, flame retardants, foaming agents, foam stabilizers, and delayed catalysts, and the raw materials of the isocyanate B component are small molecule diols and polymethylene polyphenyl polyisocyanates. The polyurethane foam potting glue for battery cells described in the invention has good fluidity, excellent flame retardant properties, and excellent resistance to environmental changes. Compared with traditional polyurethane potting glue, it is light in weight and can reduce the deadweight of new energy vehicles. However, the polyurethane foam potting glue prepared by the invention, due to the absence of inorganic fillers, theoretically leads to insufficient hardness and insufficient compression strength, resulting in weak impact resistance. At the same time, the special polyester polyol in the polyol A of the invention also belongs to polyester polyols, which are also easily hydrolyzed under high temperature and high humidity, and it is difficult to have excellent double 85 resistance. Summary of the invention

[0007] One of the technical problems to be solved by the present invention is that the existing technology has the technical problems that polyurethane potting glue for new energy electric vehicles is difficult to take into account both UL 94V0 flame retardant performance and double 85 (85°C and 85% relative humidity) 1000h aging resistance, and the hardness is not high enough. A new potting glue for new energy electric vehicles is provided, which has the characteristics of low density, meeting UL94V0 flame retardant requirements, excellent aging resistance under double 85 conditions for 1000h, high hardness and low thermal conductivity. The second technical problem to be solved by the present invention is to provide a preparation method for potting glue for new energy electric vehicle battery packs corresponding to solving one of the technical problems.

[0008] To solve one of the above technical problems, the technical solution adopted by the present invention is as follows: a potting glue for a new energy electric vehicle battery pack, composed of component A and component B, the mass ratio of component A to component B is 100:45-55; in parts by weight, component A is composed of the following components: polyether polyol I: 15-20 parts; polyester polyol: 10-15 parts; polyether polyol II: 3-6 parts; flame retardant: 10-18 parts; inorganic filler: 38-45 parts; additive: 0.4-1 part; silicone oil: 2-4 parts; water: 0.3-0.9 parts; the component B is isocyanate.

[0009] In the above technical scheme, preferably, the functionality of the polyether polyol I is 4-6, the molecular weight is 400-600, and the viscosity is 2000-10000 mPa·s; the functionality of the polyester polyol is 2-3, the molecular weight is 550-750; the functionality of the polyether polyol II is 5-7, the molecular weight is 500-700, and the viscosity is 15000-25000 mPa·s.

[0010] In the above technical scheme, preferably, the polyether polyol I is selected from at least one of NJ-6206, NJ-6209 or NJ-6305, the polyester polyol is selected from at least one of PS-2412, SKR-240B, HF-8730 or HF-8724, and the polyether polyol II is selected from at least one of NJ-6249 or NJ-6256.

[0011] In the above technical scheme, preferably, the flame retardant is selected from at least one of phosphate esters and halogenated phosphate ester flame retardants; the inorganic filler is selected from at least one of aluminum hydroxide, magnesium hydroxide, boron nitride or aluminum nitride; the auxiliary agent is selected from at least one of BYK-185, BKY-162, BYK-410 or BYK-170; the silicone oil is selected from at least one of L6900, L6100, B8545 or B8492.

[0012] In the above technical scheme, preferably, the flame retardant is selected from at least one of dimethyl methyl phosphate, diethyl ethyl phosphate, isopropylated triphenyl phosphate, diphenyl methyl phosphate, triphenyl phosphate, triethyl phosphate, tri(2-chloropropyl) phosphate or tricresyl phosphate.

[0013] In the above technical solution, preferably, the isocyanate comprises the following components in parts by weight: 0 to 3 parts of a small molecule chain extender and 97 to 100 parts of polymethylene polyphenyl polyisocyanate.

[0014] In the above technical solution, preferably, the small molecule chain extender is selected from at least one of ethylene glycol and propylene glycol.

[0015] To solve the second of the above technical problems, the technical solution adopted by the present invention is as follows:

[0016] A method for preparing the aforementioned potting glue for new energy battery packs is characterized by comprising the following steps:

[0017] (1) Prepare component A:

[0018] In parts by weight, weigh 15-20 parts of polyether polyol I, 10-15 parts of polyester polyol, 3-6 parts of polyether polyol II, 10-18 parts of flame retardant, 38-45 parts of inorganic filler, 0.4-1 part of auxiliary agent, 2-4 parts of silicone oil and 0.3-0.9 parts of water into a reaction kettle, control the material temperature at 25-40°C and stir evenly.

[0019] (2) preparing component B: comprising the following components by weight: 0-3 parts of a small molecule chain extender, 97-100 parts of polymethylene polyphenyl polyisocyanate, controlling the material temperature at 25-40° C., and stirring uniformly;

[0020] (3) Component A and component B are mixed at a mass ratio of 100:45-55 in a dispensing machine gun head; injected into the gap of the battery box containing the battery cells, and the injection volume is one-fifth to one-third of the gap of the battery box containing the battery cells; the potting glue completely fills the gap of the battery box containing the battery cells after foaming, and cures at room temperature for 3-5 days, and the potting glue can achieve the final curing effect.

[0021] The present invention provides a potting adhesive for a new energy electric vehicle battery pack and a preparation method thereof. The polyether polyol I and polyether polyol II in the present invention select polyether polyols of different viscosities, and the strength of the material is ensured by adopting high-official polyether polyols. At the same time, the two polyether polyols of different viscosities are reasonably matched so that the viscosity of the prepared component A is not too large, thereby ensuring the fluidity of the material; the proportion of polyester polyol, high-official polyether polyol, liquid flame retardant and inorganic filler is optimized to meet the UL 94V0 flame retardant requirements and 1000h aging resistance under double 85 conditions; at the same time, the problem of sedimentation and agglomeration of inorganic fillers is slowed down by adding anti-settling agents. Through the synergistic effect between the components, the prepared polyurethane potting adhesive has a low density (0.25-0.36g / cm 3 ), low thermal conductivity, high hardness, meeting UL 94V0 flame retardant requirements, and excellent hydrolysis resistance and aging resistance under double 85 conditions for 1000h, achieving good technical results. DETAILED DESCRIPTION

[0022] Table 1 List of raw materials

[0023]

[0024] [Example 1]

[0025] (1) Prepare component A:

[0026] In parts by weight, weigh polyether polyol I: NJ-6206 18 parts; polyester polyol: SKR-240B 14.5 parts; polyether polyol II: NJ-6249 4.5 parts; flame retardant: TEP 16 parts; aluminum hydroxide: 43 parts; additive: BYK-410 0.6 parts; silicone oil: B8545 3 parts; water: 0.4 parts in a reaction kettle, control the material temperature at 25-30°C, and stir evenly;

[0027] (2) preparing component B: comprising the following components by weight: 2 parts of a small molecule chain extender propylene glycol, 98 parts of polymethylene polyphenyl polyisocyanate, controlling the material temperature at 25 to 40° C., and stirring uniformly;

[0028] (2) Component A and component B are mixed at a mass ratio of 100:50 in a dispensing machine gun head; injected into the gap of the battery box containing the battery cell, and the injection volume is one-fourth of the gap of the battery box containing the battery cell; the potting glue completely fills the gap of the battery box containing the battery cell after foaming, and cures at room temperature for 3 days, and the potting glue can achieve the final curing effect. The performance test data of the prepared potting glue for new energy electric vehicles are shown in Table 3.

[0029] [Examples 2 to 6]

[0030] Examples 2 to 6 and Comparative Examples 1 to 2 are all operated according to the steps of Example 1, with the only difference being the reaction raw materials, raw material ratios, etc. The specific formula is shown in Table 2; the gaps in the battery box containing the battery cells are injected, and the injection volume is one-fifth to one-third of the gaps in the battery box containing the battery cells; the potting glue completely fills the gaps in the battery box containing the battery cells after foaming, and is cured at room temperature for 3 to 5 days; the performance test data of the prepared potting glue for new energy electric vehicles is shown in Table 3.

[0031] Table 2 Weight parts of each component in Examples 1 to 6 and Comparative Examples 1 to 2

[0032]

[0033]

[0034] The products of [Examples 1-6] and [Comparative Examples 1-2] were subjected to performance tests according to the following standards. The obtained performance test results are shown in Table 3.

[0035] Viscosity: GB / T 2794-2022;

[0036] Density: GB / T 6343-2009;

[0037] Aluminum-aluminum shear strength (25℃): GB / T 7124-2008;

[0038] Thermal conductivity: ASTM D5470-17;

[0039] Tensile strength: ISO 527-2;

[0040] Water absorption: GB / T 8810-2005

[0041] Compression strength (25℃): GB / T 8813-2020;

[0042] Flame retardant grade: GB / T 2408-2008;

[0043] Double 85 aging, 1000h: GB / T 2423.50-2012; place the sample at 85℃ and 85% humidity for 1000h.

[0044] Table 3 Performance test indicators of Examples 1 to 6 and Comparative Examples 1 to 2

[0045]

[0046]

[0047] As can be seen from the above table, polyether polyols I and II in the present invention select polyether polyols of different viscosities, and the strength of the material is ensured by adopting high-official polyether polyols. At the same time, two polyether polyols of different viscosities are reasonably matched so that the viscosity of the prepared component A will not be too large, thereby ensuring the fluidity of the material; the effects of polyester polyols, flame retardants and inorganic fillers are relative. When the content of polyester polyols and flame retardants is too much, the material can have excellent flame retardancy, but because the content of polyester polyols is too much, the hydrolysis resistance and aging resistance of the material will deteriorate, and it cannot pass the double 85 condition test; when the flame retardancy and physical properties are increased by adding inorganic fillers, too much inorganic filler is added, which will lead to excessive viscosity of the system, and ultimately lead to poor fluidity, and the gaps of the battery cells cannot be evenly covered; the present invention optimizes the ratio between the components and the synergistic effect between the components, so that the prepared potting glue for the battery pack of new energy electric vehicles has the characteristics of low density, good fluidity, no water absorption, high hardness, excellent flame retardancy, and excellent resistance to double 85 conditions, and has achieved good technical effects.

Claims

1. A potting adhesive for a new energy electric vehicle battery pack, comprising component A and component B, wherein the mass ratio of component A to component B is 100:45-55; in parts by weight, component A comprises the following components: Polyether polyol I: 15-20 parts; polyester polyol: 10-15 parts; polyether polyol II: 3-6 parts; flame retardant: 10-18 parts; inorganic filler: 38-45 parts; auxiliary agent: 0.4-1 part; silicone oil: 2-4 parts; water: 0.3-0.9 parts; the component B is isocyanate.

2. The potting glue for new energy electric vehicle battery pack according to claim 1, characterized in that: The functionality of the polyether polyol I is 4-6, the molecular weight is 400-600, and the viscosity is 2000-10000mPa·s; the functionality of the polyester polyol is 2-3, the molecular weight is 550-750; the functionality of the polyether polyol II is 5-7, the molecular weight is 500-700, and the viscosity is 15000-25000mPa·s.

3. The potting glue for new energy electric vehicle battery pack according to claim 2, characterized in that: The polyether polyol I is selected from at least one of NJ-6206, NJ-6209 or NJ-6305, the polyester polyol is selected from at least one of PS-2412, SKR-240B, HF-8730 or HF-8724, and the polyether polyol II is selected from at least one of NJ-6249 or NJ-6256.

4. The potting adhesive for new energy electric vehicle battery pack according to claim 1, characterized in that: The flame retardant is selected from at least one of phosphate ester and halogenated phosphate ester flame retardants; the inorganic filler is selected from at least one of aluminum hydroxide, magnesium hydroxide, boron nitride or aluminum nitride; the auxiliary agent is selected from at least one of BYK-185, BKY-162, BYK-410 or BYK-170; the silicone oil is selected from at least one of L6900, L6100, B8545 or B8492.

5. The potting adhesive for new energy electric vehicle battery pack according to claim 4, characterized in that: The flame retardant is selected from at least one of dimethyl methyl phosphate, diethyl ethyl phosphate, isopropylated triphenyl phosphate, diphenyl methyl phosphate, triphenyl phosphate, triethyl phosphate, tris(2-chloropropyl) phosphate or tricresyl phosphate.

6. The potting adhesive for new energy electric vehicle battery pack according to claim 1, characterized in that: The isocyanate comprises the following components, measured in parts by weight: 0 to 3 parts of a small molecule chain extender and 97 to 100 parts of polymethylene polyphenyl polyisocyanate.

7. The potting adhesive for the battery pack of a new energy electric vehicle according to claim 6, characterized in that: The small molecule chain extender is selected from at least one of ethylene glycol and propylene glycol.

8. A method for preparing the potting adhesive for new energy battery pack according to claim 1, characterized in that: The steps are as follows: (1) Prepare component A: In parts by weight, weigh 15-20 parts of polyether polyol I, 10-15 parts of polyester polyol, 3-6 parts of polyether polyol II, 10-18 parts of flame retardant, 38-45 parts of inorganic filler, 0.4-1 part of auxiliary agent, 2-4 parts of silicone oil and 0.3-0.9 parts of water into a reaction kettle, control the material temperature at 25-40°C and stir evenly. (2) preparing component B: comprising the following components by weight: 0-3 parts of a small molecule chain extender, 97-100 parts of polymethylene polyphenyl polyisocyanate, controlling the material temperature at 25-40° C., and stirring uniformly; (3) Component A and component B are mixed at a mass ratio of 100:45-55 in a dispensing machine gun head; injected into the gap of the battery box containing the battery cells, and the injection volume is one-fifth to one-third of the gap of the battery box containing the battery cells; the potting glue completely fills the gap of the battery box containing the battery cells after foaming, and cures at room temperature for 3-5 days, and the potting glue can achieve the final curing effect.

Citation Information

Cited By

  • Fire retardant and oil-resistant potting for ev batteries

    WO2026150110A1